The Right Social Media Strategy – Appraoching and Defining the Right Strategy for Small and Medium Sized Businesses - Nicole WASSENBERG (Communications of International Proceedings, 2021)
In recent years, social media has become an increasingly important part of daily life and communication. In the age of the so-called "smart phone generation", large parts of the world are connected and networked with each other. This is not least due to the fact that environmental influences and circumstances are adapting to everyday life at an ever faster pace. More and more organizations are taking advantage of the benefits and are increasingly using social media. However, many companies are faced with the challenge of which strategy to choose and how to implement it in their own company. There are various approaches in different reference books on how to proceed. How can companies harness social media strategies? Which approaches are suitable for SMEs? This short paper presents the status quo in German SMEs and addresses the question of how companies have successfully implemented social media and which approaches are suitable for which companies.
Keywords: Social Media; Strategy; Marketing; SME; B2B